Strategy of the financial services authority in improving sharia financial literacy and inclusion of North Sumatera communities - Atiqah, Siti Nurul; Yafiz, Muhammad; Arif, Muhammad (LPMP Imperium, 2025)
The Sharia financial literacy and inclusion level in North Sumatra, Indonesia, is lower than that of conventional finance. This research analyzes the Financial Services Authority's (OJK) strategies to enhance Sharia financial literacy and inclusion. Utilizing qualitative methods, including interviews and document analysis, the study reveals that OJK has implemented initiatives like the Sharia Financial Literacy Safari program, developed innovative products like Sharia Student Savings, and partnered with Sharia fintech providers to leverage digital technology. While these efforts have improved public understanding and access to sharia financial services, challenges still need to be addressed, including lack of awareness and limited infrastructure. Public interest statements The study concludes that additional steps, such as improving cross-sector cooperation and educational initiatives, are necessary to promote sharia finance's growth in the region further.